Slovakia Public Expenditure Review Mission - World Bank (Washington, DC, 2013)
The budget projections for 2008 - 2010 in Slovakia's latest Convergence Program envision the deficit continuing to decline to 0.8% of GDP in the context of economic growth close to the potential. Both spending and revenue shares are projected to fall and the debt to GDP ratio to remain below 30% of GDP. In the next decade, it will be necessary to exercise continued budget prudence so as to deal with spending pressures related to infrastructure development, social services (health and education), and to prepare for the budgetary implications of population ageing. In the environment of less buoyant growth and fiscal revenues, the need to establish clear spending priorities and to ensure value for money becomes more important than ever.